A review of radioactivity in the Gulf region. (October 2020) - Uddin, S.; Fowler, S.W.; Behbehani, M.; Al-Ghadban, A.N.; Swarzenski, P.W.; Al-Awadhi, N.
Abstract: The region around the Gulf is moving toward a nuclear energy option with the first nuclear power plant now operational in Bushehr, Iran. Others are soon to be commissioned in Abu Dhabi and in Saudi Arabia. For this reason, radiological safety is becoming a prime concern in the region. This review compiles published data on radionuclide concentrations in seawater, sediment, and biota that have been analyzed in the Gulf countries, along with spatial distribution patterns to enable a synoptic view of the available datasets. The seawater concentrations of 3 H, 210 Po, 210 Pb, 137 Cs, and 90 Sr varied between 130 and 146, 0.48–0.68, 0.75–0.89, 1.25–1.38, 0.57–0.78 mBq L −1, respectively. The 226 Ra concentration in seawater varied between 0.26 and 3.82 Bq L −1 . Extremely high 40 K concentrations between 132 and 149 Bq L −1 have been reported from the Iranian coast compared to 8.9–9.3 Bq L −1 from the western side of the Gulf. Concentrations of 40 K, total 210 Pb, 137 Cs, 90 Sr, 226 Ra, 228 Ra, 238 U, 235 U, 234 U, 239+240 Pu, and 238 Pu were determined in sediment and ranged between 353 and 445, 23.6–44.3, 1.0–3.1, 4.8–5.29, 17.3–20.5, 15–16.4, 28.7–31.4, 1.26–1.30, 29.7–30.0, 0.045–0.21 and 0.028–0.03 Bq kg −1 dry weight, respectively. Significantly higher 137 Cs values have been reported from the Iranian coast compared to the western coast of the Gulf. Whole fish concentrations of 40 K, 226 Ra, 224 Ra, 228 Ra, 137 Cs, 210 Po and 90 Sr ranged between 230 and 447, 0.7–7.3, <0.5–6.6, <0.5–15.80, <0.17, 0.88–4.26 and 1.86–5.34 Bq kg −1 dry weight, respectively. 210 Po was found to be highly concentrated in several marine organisms with the highest 210 Po concentration found in the clam Marcia marmorata (193.5–215.6 Bq kg −1 dry weight). The review highlights the overall paucity of data and inconsistencies in the measurement of radionuclides throughout the Gulf region. Further, since the region is moving toward nuclear energy to meet its increasing energy demand, and coupled with the environmental effects from offshore oil exploration and the heavy impact of climate change, there is a pressing need to undertake a comprehensive marine radioactivity monitoring and assessment effort by conducting a joint cruise in the Gulf with participation of all the adjoining countries. Several recommendations on sampling marine matrixes in the Gulf are given with the aim of improving comparability of radionuclide data from the various studies undertaken in the Gulf region. Highlights: Here we present the information on environmental radioactivity from the Persian/Arabian Gulf region. There is paucity of data on both naturally occurring and anthropogenic radionuclides in the region. The radioactivity levels are comparable to other marine areas in the world. The review reveals data gaps across the spatial domain in the Gulf, and highlights an obvious need to undertake a regional radioactivity assessment